An effective method for preparation of high purity oligohexamethylene guanidine salts - I. S. Ivanov; D. O. Shatalov; S. A. Kedik; I. P. Sedishev; S. V. Beliakov; K. N. Trachuk; V. V. Komarova (Тонкие химические технологии)
Objectives. Given that microorganisms can become resistant to certain groups of drugs and considering also their ability to form biofilms, the development of new drugs that are active against adapted microflora is required. This study focused on the development of a new method for the synthesis of a promising compound, the branched hydrosuccinate oligohexamethylene guanidine (OHMGsucc), with high purity that meets the standards of the 14th edition State Pharmacopeia of the Russian Federation (SPRF). Previously proposed methods have managed to isolate this product, which, however, complies with the requirements of the outdated SPRF. Therefore, the main aim of this study was to update the regulatory framework for the indicated OHMG salt for its further use in the pharmaceutical industry according to modern standards.Methods. To control the residual impurities of hexamethylenediamine (HMDA) and guanidine hydrochloride (GHC), high-performance liquid chromatography (HPLC) was applied using a Thermo Scientific Dionex UltiMate 3000 chromatograph, and the chromatographic signals of the test solution with those of a standard sample solution obtained by a previously published conventional method were compared.Results. The HPLC experimental data indicated a significant difference in the quantitative content of HMDA and GHC observed for the new and older preparation method of the branched OHMGsucc, suggesting that the method disclosed in this article can be used to obtain highly pure OHMGsucc.Conclusions. The specified compound was standardized with the parameter “related impurities” according to the current (14th) edition of the SPRF. The effectiveness and reproducibility of the proposed method was experimentally confirmed. In addition, a process diagram for the preparation of the indicated OHMG salt was prepared.